The effect of simultaneous dual‐focus integration on the global flash multifocal electroretinogram in the human eye. (29th October 2020) - Fung, Mavis M Y; Choi, Kai Yip; Chan, Henry H L
Abstract: Purpose: To investigate the effect of simultaneous dual‐focus (DF) on retinal activities measured by global flash multifocal electroretinogram (mfERG). Methods: Thirty adults were recruited for mfERG measurement under three conditions: in‐focus (i.e., no defocus), +2.50 D DF and +7.50 D DF, administered using single vision contact lenses and DF lenses. The direct component (DC) and the induced component (IC) of the mfERG were pooled into central macular (0–8°), para‐macular (8–18°) and peri‐macular (18–30°) regions, and then compared across the three conditions using two‐way, repeated measures ANOVA. Results: Simultaneous DF had a significant effect on the IC amplitude, which was significantly stronger under +7.50 D DF ( p  < 0.01) than for the in‐focus condition, which was mostly derived from the central and para‐macular regions. No significant effect was observed for the +2.50 D DF condition. Conclusion: Under the effect of relatively strong simultaneous DF integration, the retina showed an enhanced retinal response, which originated from the inner retina. Compared with the peri‐macular region, central and para‐macular responses appeared to be enhanced.